Design of Mn and Zr incorporated Ag2O nanoparticles and their enhanced photocatalytic activity driven by visible light irradiation for degradation of rose bengal dye. (12th January 2021) - Subalakshmi, A.; Kavitha, B.; Karthika, A.; Nikhil, S.; Srinivasan, N.; Rajarajan, M.; Suganthi, A.
Abstract : Mn, Zr co-doped Ag2 O nanoparticles were blended through a wet chemical strategy, and the physicochemical properties of doped and co-doped silver oxide nanoparticles were characterized. Abstract : Mn, Zr co-doped Ag2 O nanoparticles (NPs) were blended through a wet chemical strategy, and the physicochemical properties of doped and co-doped silver oxide nanoparticles were characterized using X-ray diffraction, UV-DRS visible spectroscopy, Fourier transform infrared spectroscopy, scanning electron microscopy with energy dispersive X-ray spectroscopy, high-resolution transmission electron microscopy, Brunauer–Emmett–Teller (BET) and electrochemical impedance spectroscopy (EIS) and photoluminescence techniques. XRD reveals that the crystal structure of Mn, Zr co-doped Ag2 O NPs has a face-centered cubic phase (FCC). Photoluminescent spectra analysis further demonstrates that the Mn, Zr co-doped Ag2 O extraordinarily improves the charge generation and suppresses the charge recombination of photogenerated electron–hole pairs, which would be advantageous to improving the photocatalytic properties. The photocatalytic properties of Mn, Zr co-doped Ag2 O NPs were assessed by the degradation of rose bengal dye under visible light illumination. The results revealed that Mn, Zr co-doped Ag2 O (Mn, Zr–Ag2 O) showed greater photocatalytic activity compared with different photocatalysts. In addition, Mn, Zr co-doped Ag2 O was seen as a reusable photocatalyst.